Plant Growth Regulator and Soil Surfactants' Effects on Saline and Deficit Irrigated Warm‐Season Grasses: I. Turf Quality and Soil Moisture. Issue 6 (1st November 2014) - Schiavon, Marco; Leinauer, Bernd; Serena, Matteo; Maier, Bernd; Sallenave, Rossana
ABSTRACT: A study was conducted at New Mexico State University in Las Cruces, NM, from 2010 to 2012 to investigate the effects of deficit irrigation on bermudagrass ( Cynodon dactylon L.) cultivar Princess 77 and seashore paspalum ( Paspalum vaginatum Swartz) cultivar Sea Spray treated with either soil surfactants [Revolution (modified methyl capped block copolymer) or Dispatch (alkyl polyglucoside blended with a straight block copolymer)] or a plant growth regulator [Trinexapac‐ethyl (TE); 4‐(cyclopropylhydroxymethylene)‐3, 5‐dioxocyclohexanecarboxylic acid]. Irrigation was applied daily at 50% reference evapotranspiration from either a sprinkler or a subsurface drip system with either potable (electrical conductivity [EC] = 0.6 dS m −1 ) or saline (2.3 dS m −1 ) water. Normalized Difference Vegetation Index (NDVI) and visual ratings were determined monthly to assess stand quality and turf stress. Princess 77 treated with TE showed the highest quality and the highest NDVI (0.655) on 10 out of 15 sampling dates. Positive effects of TE applications were also observed on Sea Spray quality, NDVI, and fall color retention. Subsurface drip irrigation resulted in higher quality and NDVI during the third year of the study when compared with sprinkler irrigation. Salinity buildup in the root zone did not negatively affect visual quality of the tested warm‐season species. Generally, sprinkler irrigation system and turf treated with Revolution promoted higher water distribution uniformity (lower standard deviations) than the other treatments. Further research is needed to investigate if greater drought tolerance of subsurface drip–irrigated turf is the result of increased water‐use efficiency due to altered root morphology.